Interpretation of "Expert consensus on posterior facet distraction and fusion technique for the treatment of atlantoaxial dislocation (2024)" - DU Yue‐qi; CHEN Zan (Chinese Journal of Contemporary Neurology and Neurosurgery)
Atlantoaxial dislocation (AAD) is a common craniovertebral junction deformity that can result in severe neurological dysfunction. To better standardize the diagnosis and treatment of AAD, the Spine and Spinal Cord Group, Neurosurgical Branch, Chinese Medical Association, and the Chinese Craniovertebral Junction Malformation Research Alliance published the "Expert consensus on posterior facet distraction and fusion technique for the treatment of atlantoaxial dislocation (2024)" in August 2024. This consensus provides detailed recommendations regarding application range, preoperative evaluation, surgical techniques, and complication management for this procedure, aiming to offer practical guidance for its clinical application. The key points of the expert consensus are summarized and interpreted in this article, to provide reference for clinicians and researchers.